New insights into the NaCl impact on emulsifying properties of globular proteins. (March 2022) - Zhang, Lili; Lin, Wei-Feng; Zhang, Yin; Tang, Chuan-He
Abstract: In the work, the emulsifying properties of three representative globular proteins (soy β -conglycinin, glycinin and bovine serum albumin; designated as SC, SG and BSA, respectively) with different structural characteristics, as affected by the addition of NaCl (0–1000 mM), were investigated and compared, using two emulsion systems at oil fractions ( ø ) of 0.2 and 0.8, respectively. The modulation of physicochemical properties and conformations of these three proteins by NaCl was first evaluated in terms of solubility, ζ -potential, surface hydrophobicity, particle size and intrinsic fluorescence profile. The electrostatic screening by the presence of appropriate concentrations (50–100 mM) of NaCl resulted in progressive increases in extent of protein aggregation and surface hydrophobicity of both SC and SG, but the addition of high concentrations (>300 mM) of NaCl was favorable for the 'salting-in' effects. At ø = 0.2, the presence of NaCl impaired the emulsification performance of SC, while in the SG case, the emulsification performance was slightly affected. At ø = 0.8, the presence of NaCl remarkably improved the emulsification performance of SC, and facilitated the droplet flocculation and gel network formation in the HIPEs, while in the SG case, the gel stiffness of the HIPEs was also improved. All the evidences indicated that at low ø values, the influence of NaCl on the emulsifying properties of oligomeric globulins was dominated by the electrostatic screening effect, while at high ø values (e.g., 0.8), the hydration repulsion between bound hydrated Na + played a crucial role in the performance of these globulins as Pickering stabilizers. The findings are of importance for the understanding of the salt impact on the properties and stability of food protein emulsion formulations. Graphical abstract: Image 1 Highlights: The influence of NaCl on emulsifying properties of globular proteins was revisited. Excess NaCl was favorable for 'salting-in' effects of proteins. The modulation of emulsifying properties depended on the oil fraction and protein type. At 0.2 oil fraction, the electrostatic screening improved the emulsification of oligomeric proteins. At 0.8 oil fraction, the hydration repulsion facilitated Pickering stabilization.